Defining diagnostic thresholds for dissociation between caloric test and vHIT in Ménière’s disease - Cheon, Tae Uk; Park, Ju Ha; Lee, Ji Seop; Bae, Seong Hoon (Frontiers in Neurology, 2025)
ObjectiveMénière’s disease (MD) presents with episodic vertigo, hearing loss, and tinnitus; however, its diagnosis remains challenging owing to symptom overlap with other vestibular disorders. We evaluated the diagnostic value of dissociation between caloric test and video head impulse test (vHIT) results in MD compared to vestibular schwannoma (VS) and benign paroxysmal positional vertigo (BPPV).MethodsA retrospective analysis included 195 patients with MD (n = 51), VS (n = 112), or BPPV (n = 32). Vestibular function was assessed using caloric tests and vHIT. Dissociation was defined as an abnormal caloric response [canal paresis (CP) > 25%] with a normal vHIT gain (>0.80). Diagnostic accuracy was assessed using diagnostic odds ratio (DOR) and receiver operating characteristic curves.ResultsDissociation was more frequent in MD (56.9%) than in VS (25.0%) or BPPV (9.4%) (p < 0.001). It effectively distinguished MD from BPPV (DOR = 12.74) but was less useful for MD vs. VS (DOR = 3.96). CP differentiated MD from BPPV but not VS.ConclusionDissociation between caloric and vHIT results is a specific indicator of MD, aiding differentiation from BPPV. However, its utility for distinguishing MD from VS is limited.